Using eye tracking to understand the impact of cognitive abilities on search tasks - Nisiforou, Efi; Michailidou, Eleni; Laghos, Andrew (My University, 2014)
Nowadays, there is an increase of studies that examine individuals' cognitive characteristics in correlation to visual perception. The present study investigated the association between cognitive abilities and Web page complexity. Specifically, differences within simple, medium and complex Web pages were observed among the field dependent, independent and mixed cognitive groups via a task completion time with the use of the eye tracking technology. The results showed that task completion time is significantly different in medium and complex pages between the FD and FI users, while, in the simple pages, no statistical differences appeared. Furthermore, it was supported that users' FD-I cognitive construct style can be identified using innovative techniques like eye tracking studies by analyzing users' scan path and heat maps.
Keywords: Cognitive abilities; Eye tracking; Field Dependent-Independent; ViCRAM algorithm; Visual complexity